2011
DOI: 10.1007/s12272-011-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solubility and bioavailability of flurbiprofen by cycloamylose

Abstract: The effect of cycloamylose on the aqueous solubility of flurbiprofen was investigated. To improve the solubility and bioavailability of flurbiprofen (poor water solubility), a solid dispersion was spray dried with a solution of flurbiprofen and cycloamylose at a weight ratio of 1:1. The physicochemical properties of solid dispersions were investigated using SEM, DSC, and X-ray diffraction. The dissolution and bioavailability in rats were evaluated compared with a commercial product. Cycloamylose increased solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Cyclodextrins have been used for complex formation of various bioactive or pharmacologically active compounds, such as drugs and vitamin-like substances, thereby enhancing the bioavailability of these molecules [1721]. Some of these studies also found that the physicochemical properties depended on the method used for complex formation [20].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodextrins have been used for complex formation of various bioactive or pharmacologically active compounds, such as drugs and vitamin-like substances, thereby enhancing the bioavailability of these molecules [1721]. Some of these studies also found that the physicochemical properties depended on the method used for complex formation [20].…”
Section: Resultsmentioning
confidence: 99%
“…The favourable effect of natural β-cyclodextrin (Muraoka et al, 2004;Cirri et al, 2005;Tokumura et al, 2009;Li et al, 2010;Baek et al, 2011) and its derivatives, such as hydroxypropyl-β-cyclodextrin (Govindarajan and Nagarsenker, 2005;Vega et al, 2013), hydroxyethyl-β-cyclodextrin and methyl-β-cyclodextrin (Cirri et al, 2005) on its pharmaceutical properties has been previously reported. For example, Cirri et al (2005) reported that flurbiprofen and methyl-β-cyclodextrin (Me-β-CD) complexes prepared in the 1:1 molar ratio using kneading and co-evaporation techniques exhibit higher solubility and dissolution profiles than flurbiprofen alone or in a state of a physical mixture.…”
Section: Introductionmentioning
confidence: 94%
“…Several formulation strategies have been reported to improve the solubility and dissolution rate of flurbiprofen, such as dry elixir (Kim and Yoon, 1995), solid dispersion (Habib et al, 1998;Oh et al, 2011), salt formation (Gupta et al, 1997), microemulsion (Park et al, 1997;Ambade et al, 2008), inclusion complex with cyclodextrins (Tokumura et al, 2009;Li et al, 2010) and cycloamyloses (Baek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Flurbiprofen kém tan trong nước, điều này ảnh hưởng không nhỏ đến tốc độ hấp thu cũng như sinh khả dụng và hiệu quả điều trị của thuốc. Bên cạnh các biện pháp như bào chế thuốc dưới dạng elixir [7], hệ phân tán rắn [8,9], đưa về dạng muối [10], hệ vi nhũ tương [11], tạo phức với cycloamylose [12],… việc sử dụng βcyclodextrin (β-CD) để bao lấy các phân tử dược chất cũng đã được chứng minh là có tác dụng cải thiện độ hòa tan và sinh khả dụng của flurbiprofen [13][14][15]. Đáng chú ý là β-CD có tính tương thích sinh học cao, việc sử dụng oligosaccharide dạng vòng này theo đường uống hoàn toàn không gây độc.…”
Section: Mở đầUunclassified